THE INFLUENCE OF THE IDEAS OF THE HURUFISM SECT ON NASIMTS WORK - Amonova, Zilola (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract. The article deals with (he influence of hurufism, one of (he mystical sects, on the work of the great poet ImodiddinNasimi. Also, die verses of the poet written under the influence of literacy are analyzed from the ideological and artistic point of view.Nasimi expresses his thoughts and feelings in a simple and popular way. Thal is why the poet’s poems are close to the heart. While these poems may seem simple and straightforward at tlrsi glance, they are deep in content and artistically high. It is no exaggeration to say that Nasi mis work was one of the reasons for the spread of the ideas of the Hurufi sect among the people. He focused on the inner meanings of die Arabic alphabet, the equality of the human face with the mushaf, and the divinity of man.